The Intersection of Care Seeking and Clinical Capacity for Patients With Highly Pathogenic Avian Influenza A (H5N1) Virus in Indonesia: Knowledge and Treatment Practices of the Public and Physicians. (14th June 2016) - Kreslake, Jennifer M.; Wahyuningrum, Yunita; Iuliano, Angela D.; Storms, Aaron D.; Lafond, Kathryn E.; Mangiri, Amalya; Praptiningsih, Catharina Y.; Safi, Basil; Uyeki, Timothy M.; Storey, J. Douglas
Abstract: Background: Indonesia has the highest human mortality from highly pathogenic avian influenza (HPAI) A (H5N1) virus infection in the world. Methods: A survey of households (N=2520) measured treatment sources and beliefs among symptomatic household members. A survey of physicians (N=554) in various types of health care facilities measured knowledge, assessment and testing behaviors, and perceived clinical capacity. Results: Households reported confidence in health care system capacity but infrequently sought treatment for potential HPAI H5N1 signs/symptoms. More clinicians were confident in their knowledge of diagnosis and treatment than in the adequacy of related equipment and resources at their facilities. Physicians expressed awareness of the HPAI H5N1 suspect case definition, yet expressed only moderate knowledge in questioning symptomatic patients about exposures. Self-reported likelihood of testing for HPAI H5N1 virus was high after learning of certain exposures. Knowledge of antiviral treatment was moderate, but it was higher among clinicians in puskesmas . Physicians in private outpatient clinics, the most heavily used facilities, reported the lowest confidence in their diagnostic and treatment capabilities. Conclusions: Educational campaigns can encourage recall of possible poultry exposure when patients are experiencing signs/symptoms and can raise awareness of the effectiveness of antivirals to drive people to seek health care. Clinicians may benefit from training regarding exposure assessment and referral procedures, particularly in private clinics. ( Disaster Med Public Health Preparedness . 2016;10:838–847)